Manganese zinc ferrite composite magnetic catalyst and preparation method thereof

By hydrothermal reaction between CaIn2S4 and Mn0.5Zn0.5Fe2O4 nanoparticles, CaIn2S4@Mn0.5Zn0.5Fe2O4 composite magnetic catalyst was formed, which solved the problem of low photocatalytic degradation efficiency using CaIn2S4 alone, and achieved efficient wastewater treatment and rapid recovery and utilization of catalysts.

CN119608188APending Publication Date: 2025-03-14POWER RES INST OF STATE GRID SHAANXI ELECTRIC POWER CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411810853.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the sewage generated by the manganese-zeb ferrite magnetic ring for power distribution network fault detection, the photocatalytic degradation efficiency of CaIn2S4 alone is limited, resulting in low sewage treatment efficiency, and the recycling of photocatalytic nanoparticles is difficult and the recycling rate is low.

Method used

Using the preparation method of manganese-zeb ferrite composite magnetic catalyst, CaIn2S4 and Mn0.5Zn0.5Fe2O4 nanoparticles were subjected to hydrothermal reaction to form CaIn2S4@Mn0.5Zn0.5Fe2O4 composite magnetic catalyst, the photocatalytic performance is improved and rapid recovery is achieved using its magnetic properties and heterostructure.

Benefits of technology

It significantly improves the photocatalytic performance, realizes rapid recovery and low-cost recycling of catalysts, reduces wastewater treatment costs, and reduces secondary pollution of water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608188A_ABST
    Figure CN119608188A_ABST
Patent Text Reader

Abstract

The invention relates to a manganese zinc ferrite composite magnetic catalyst and a preparation method thereof. The preparation method comprises the following steps: adding manganese nitrate, zinc nitrate and ferric nitrate into deionized water to form a metal ion solution; the preparation method comprises the following steps: adding ethylenediaminetetraacetic acid into a metal ion solution to form sol, performing heating dehydration treatment, grinding, and performing heat treatment to obtain manganese zinc ferrite nanoparticles; dissolving calcium nitrate, indium nitrate and thioacetamide in deionized water, then adding the manganese zinc ferrite nanoparticles to obtain a suspension of a reaction mixture, carrying out hydrothermal reaction, and carrying out subsequent extraction treatment to obtain the manganese zinc ferrite composite magnetic catalyst. The composite magnetic catalyst is prepared by utilizing a two-step hydrothermal method, the photocatalytic performance of the composite magnetic catalyst is remarkably improved, and the composite magnetic catalyst can be quickly and completely recycled through magnet adsorption, so that the photocatalytic performance of a single catalyst is improved, and quick recycling and cyclic utilization of the photocatalyst are realized; and the application cost of photocatalysis is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of nano composite materials, and specifically relates to a manganese-zinc ferrite composite magnetic catalyst and a preparation method thereof. Background Art

[0002] With the development of social economy and the acceleration of industrialization, the demand for electric energy in the whole society is increasing rapidly. In order to achieve sustainable social development, the development and utilization of renewable energy and various green energy sources are becoming more and more important. In the future, the distribution network will be connected to a high proportion of distributed power sources. The access of distributed power sources to the distribution system will have a great impact on the power system, introducing a series of safety and technical issues to the operation of the distribution system. Therefore, various sensors used for fault detection and safety monitoring of distribution networks have entered large-scale applications in power systems. Among them, electromagnetic detection sensors based on ferrite materials account for the largest proportion, so ferrite materials are increasingly used in power systems. In particular, in recent years, the demand for manganese-zinc ferrite for precise fault location equipment and technology for distribution networks based on the principle of boundary protection technology has been huge. A certain amount of sewage is generated in the preparation process of manganese-zinc ferrite materials, especially the synthesis process of manganese-zinc ferrite nanocrystals involves the use of organic reagents, which produces organic pollutant wastewater.

[0003] Photocatalytic degradation of organic pollutants is considered to be an efficient and economical technical approach to water pollution control. In recent years, sulfide-based photocatalysts have attracted widespread attention due to their narrow band gap, visible light absorption, and high photocatalytic performance. In particular, narrow-band gap CaIn 2 S 4 (Eg~1.9eV) has become a research hotspot in sulfide-based photocatalysts as a low-cost alkaline earth metal-based ternary sulfide semiconductor. However, similar to other narrow-bandgap catalysts, the separation efficiency of photogenerated carriers (electrons-holes) is low when CaIn is used alone. 2 S 4 The photocatalytic degradation efficiency of CaIn is very limited. 2 S 4 Realizing interface coupling with other semiconductor materials is of great significance for effectively inhibiting the recombination of photogenerated electron-hole pairs. In addition, improving the reuse rate of photocatalytic materials has always been one of the focuses of photocatalytic research. Photocatalytic materials are mostly nano-sized particles. At present, the natural sedimentation method cannot completely recover or remove the photocatalytic nanoparticles in the water after the reaction. In this way, it is impossible to recycle the photocatalyst and it will cause secondary pollution of the water. The use of ultra-high-speed centrifuge to recover nanoparticles leads to high costs, which is not conducive to the large-scale application of photocatalysis. Therefore, in the treatment of sewage generated by the production of boundary elements (manganese-zinc ferrite magnetic rings) for fault detection in distribution networks, CaIn is used alone. 2 S4 The relatively limited photocatalytic degradation efficiency leads to insufficient efficiency of sewage treatment, and the recovery of photocatalytic nanoparticles is relatively difficult, resulting in a low recycling rate. Summary of the invention

[0004] The present invention provides a manganese-zinc ferrite composite magnetic catalyst and a preparation method thereof, the purpose of which is to solve the problem of using CaIn alone in treating the wastewater generated by the boundary element (manganese-zinc ferrite magnetic ring) for fault detection in the production of distribution network. 2 S 4 The relatively limited photocatalytic degradation efficiency leads to insufficient efficiency of sewage treatment, and the recovery of photocatalytic nanoparticles is relatively difficult, resulting in a low recycling rate.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: The present invention provides a method for preparing a manganese-zinc ferrite composite magnetic catalyst, comprising the following steps: S1. Add manganese nitrate, zinc nitrate and ferric nitrate into deionized water and mix and dissolve to form a metal ion solution, wherein: The molar ratio of manganese nitrate, zinc nitrate and iron nitrate is 1:1:4; S2, adding ethylenediaminetetraacetic acid having the same mass as the total mass of metal ions in the metal ion solution to the metal ion solution, stirring and dissolving to form a sol; heating and dehydrating the sol to obtain a dry gel, grinding the dry gel to obtain a powder; heat-treating the dry gel powder to obtain manganese zinc ferrite nanoparticles; S3, dissolving calcium nitrate, indium nitrate and thioacetamide in deionized water, the product is CaIn 2 S 4 ; Then add manganese zinc ferrite nanoparticles to obtain a suspension of a reaction mixture, wherein: The molar ratio of calcium nitrate, indium nitrate and thioacetamide is 1:2:8. The added manganese zinc ferrite nanoparticles and CaIn 2 S 4 The mass ratio is 70:1~10:1; S4. The suspension of the reaction mixture is subjected to a hydrothermal reaction, and then subjected to subsequent extraction treatment to obtain a manganese-zinc-ferrite composite magnetic catalyst.

[0006] In some embodiments, in S1, the manganese nitrate is Mn(NO 3 ) 2 ·4H 2 O, zinc nitrate is Zn(NO 3 ) 2 6H 2 O, ferric nitrate is Fe(NO 3 ) 3 9H2 O.

[0007] In some embodiments, in S1, manganese nitrate, zinc nitrate and ferric nitrate are added to deionized water, and then stirred at room temperature for 25 to 35 minutes to form a metal ion solution.

[0008] In some embodiments, in S2, after ethylenediaminetetraacetic acid is added to the metal ion solution, the solution is stirred and dissolved at a temperature of 60 to 80° C. for 6 to 8 hours to form a sol.

[0009] In some embodiments, in S2, the sol is heated and dehydrated to obtain a xerogel, specifically: The sol was heated and dehydrated at 80-100°C for 5-6 hours to obtain a dry gel.

[0010] In some embodiments, in S2, the parameters of the heat treatment are controlled as follows: The temperature is controlled at 400~500℃ and the time is controlled at 60~80 minutes.

[0011] In some embodiments, in S3, after adding the manganese zinc ferrite nanoparticles, stirring is performed at room temperature for 30 to 35 minutes to form a suspension of the reaction mixture.

[0012] In some embodiments, in S4, the hydrothermal reaction specifically comprises: The suspension of the reaction mixture was placed in a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, wherein the parameters of the hydrothermal reaction were controlled as follows: The temperature is controlled at 160~170°C and the time is controlled at 10~12 hours.

[0013] Furthermore, in S4, the subsequent extraction process specifically includes: After the reaction is completed, the autoclave is naturally cooled to room temperature, and the manganese-zinc ferrite composite magnetic catalyst powder is obtained through centrifugal filtration, washing and drying.

[0014] The present invention also provides a manganese-zinc-ferrite composite magnetic catalyst, which is prepared by the preparation method of the manganese-zinc-ferrite composite magnetic catalyst; Manganese zinc ferrite composite magnetic catalyst is: CaIn 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 , which contains magnetic Mn 0.5 Zn 0.5 Fe 2 O 4Agglomerates of particles, where: CaIn for constructing manganese-zinc ferrite composite magnetic catalyst 2 S 4 With Mn 0.5 Zn 0.5 Fe 2 O 4 The band structures of the two overlap, forming a heterostructure.

[0015] Compared with the prior art, the manganese-zinc ferrite composite magnetic catalyst and the preparation method thereof of the present invention have the following beneficial effects: The invention discloses a method for preparing a manganese-zinc-ferrite composite magnetic catalyst, comprising the following steps: S1, adding manganese nitrate, zinc nitrate and ferric nitrate into deionized water, mixing and dissolving them to form a metal ion solution, wherein the molar ratio of manganese nitrate, zinc nitrate and ferric nitrate is 1:1:4; S2, adding ethylenediaminetetraacetic acid having the same mass as the total mass of metal ions in the metal ion solution into the metal ion solution, stirring and dissolving to form a sol; heating and dehydrating the sol to obtain a dry gel, grinding the dry gel to obtain a powder; heat-treating the dry gel to obtain manganese-zinc-ferrite nanoparticles; S3, dissolving calcium nitrate, indium nitrate and thioacetamide in deionized water, and then adding manganese-zinc-ferrite nanoparticles to obtain a suspension of a reaction mixture, wherein the molar ratio of calcium nitrate, indium nitrate and thioacetamide is 1:2:8, and the added manganese-zinc-ferrite nanoparticles and the resultant CaIn 2 S 4 The mass ratio of the reaction mixture is 70:1 to 10:1; S4, the suspension of the reaction mixture is subjected to hydrothermal reaction, and then subjected to subsequent extraction treatment to obtain a manganese-zinc ferrite composite magnetic catalyst. Based on the above, the present invention uses a two-step hydrothermal method to prepare CaIn 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 (CIS@MZF) composite magnetic catalyst. Firstly, manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles. Then, CaIn was prepared by hydrothermal method. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 (CIS@MZF) composite magnetic catalyst. CaIn of the present invention 2 S 4 With Mn 0.5Zn 0.5 Fe 2 O 4 An effective heterostructure is formed, and CaIn 2 S 4 With Mn 0.5 Zn 0.5 Fe 2 O 4 The band structure of CaIn is staggered, and the photogenerated electrons can 2 S 4 The conduction band of Mn 0.5 Zn 0.5 Fe 2 O 4 conduction band transfer, and the photogenerated holes are transferred from Mn 0.5 Zn 0.5 Fe 2 O 4 CaIn 2 S 4 Valence band transfer, the effect of this carrier transmission reduces the effective bandwidth and suppresses the recombination of photogenerated carriers to a large extent. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 The photocatalytic performance of the (CIS@MZF) composite magnetic catalyst has been significantly improved. And because the manganese zinc ferrite used in the present invention has good magnetic properties, the composite photocatalyst can be quickly and completely recovered by simple magnetic adsorption, so that the composite magnetic catalyst prepared by the present invention can be recycled at low cost and quickly. Therefore, the composite magnetic catalyst prepared by the present invention not only improves the photocatalytic performance of a single catalyst, but also realizes the rapid recovery and recycling of the photocatalyst, greatly reducing the application cost of the photocatalytic technology. To a certain extent, it promotes CaIn 2 S 4 The practical application and development of photocatalytic materials has great practical significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings in the specification are used to provide further understanding of the present invention and constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0017] Figure 1 A schematic diagram of a scanning electron microscope of a manganese-zinc-ferrite composite magnetic catalyst prepared in Example 1 of a manganese-zinc-ferrite composite magnetic catalyst and a preparation method thereof of the present invention; Figure 2A schematic diagram showing a comparison of the photocatalytic performance of a manganese-zinc-ferrite composite magnetic catalyst and a preparation method thereof according to the present invention; Figure 3 The pure CaIn in the manganese-zinc ferrite composite magnetic catalyst and its preparation method of the present invention 2 S 4 Schematic diagram comparing the recovery effects of manganese-zinc-ferrite composite magnetic catalyst through a ring magnet. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0019] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0021] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0022] How to comprehensively utilize manganese-zinc ferrite materials so that when they are used in the preparation of distribution network related components, their high photocatalytic efficiency and recycling rate can be used to improve the sewage treatment efficiency of boundary elements (such as manganese-zinc ferrite magnetic rings) used for distribution network fault detection during the production process.

[0023] like Figure 1 As shown, the preparation method of a manganese-zinc ferrite composite magnetic catalyst of the present invention comprises the following steps S1. Add manganese nitrate, zinc nitrate and ferric nitrate into deionized water and mix and dissolve to form a metal ion solution, wherein: The molar ratio of manganese nitrate, zinc nitrate and iron nitrate is 1:1:4; S2, adding ethylenediaminetetraacetic acid having the same mass as the total mass of metal ions in the metal ion solution to the metal ion solution, stirring and dissolving to form a sol; heating and dehydrating the sol to obtain a dry gel, grinding the dry gel to obtain a powder; heat-treating the dry gel powder to obtain manganese zinc ferrite nanoparticles; S3, dissolving calcium nitrate, indium nitrate and thioacetamide in deionized water, the product is CaIn 2 S 4 ; Then add manganese zinc ferrite nanoparticles to obtain a suspension of a reaction mixture, wherein: The molar ratio of calcium nitrate, indium nitrate and thioacetamide is 1:2:8. The added manganese zinc ferrite nanoparticles and CaIn 2 S 4 The mass ratio is 70:1~10:1; S4. The suspension of the reaction mixture is subjected to a hydrothermal reaction, and then subjected to subsequent extraction treatment to obtain a manganese-zinc-ferrite composite magnetic catalyst.

[0024] The present invention provides a method for preparing a manganese-zinc ferrite composite magnetic catalyst, by utilizing manganese-zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) magnetic particles and metal sulfide catalysts (CaIn 2 S 4 ) Composite structure magnetic heterostructure catalytic material. The composite magnetic catalyst prepared by the present invention has magnetism and magnetic heterostructure. Magnetism can effectively improve its recovery efficiency, and the heterostructure can improve its photocatalytic efficiency, thereby efficiently and low-costly treating the sewage generated in the production process of boundary elements (manganese-zinc ferrite magnetic rings) for distribution network fault detection, thereby improving the environmental pollution problem caused by it.

[0025] Specifically: Single-phase metal sulfide photocatalyst (CaIn 2 S 4 ) particles have serious photogenerated carrier recombination problems, which affects their photocatalytic performance. 0.5 Zn 0.5 Fe 2 O 4 ) magnetic particles form a heterogeneous structure after compounding, which promotes the separation of photogenerated carriers and inhibits their recombination, thereby improving the photocatalytic performance of a single catalyst. 0.5 Zn0.5 Fe 2 O 4 ) Magnetic particles can easily realize the rapid recovery and reuse of catalysts, greatly reducing the recovery and application costs of photocatalysts, while reducing the secondary pollution of water bodies by residual catalyst particles. Therefore, the present invention can not only improve the photocatalytic performance of a single catalyst, but also realize the rapid recovery and reuse of catalysts, and improve the photocatalytic performance of metal sulfide photocatalysts (CaIn 2 S 4 ) applicability.

[0026] The following is a detailed description of a manganese-zinc ferrite composite magnetic catalyst and a preparation method thereof according to the present invention through specific examples.

[0027] Example 1 Step 1: According to the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) in a stoichiometric ratio of manganese nitrate (Mn(NO 3 ) 2 ·4H 2 O) 0.005 mol, zinc nitrate (Zn(NO 3 ) 2 6H 2 O) 0.005 mol, ferric nitrate (Fe(NO 3 ) 3 9H 2 O) 0.02 mol was added to 100 ml of deionized water to dissolve, and stirred at room temperature for 30 minutes to form a clear and transparent solution. Then, 0.03 mol of ethylenediaminetetraacetic acid (EDTA) (the same as the total mass of the metal ions) was weighed and added to the metal ion solution, and fully stirred and dissolved at 60°C for 6 hours to form a sol. The sol was heated and dehydrated at 100°C for 6 hours to obtain a dry gel, which was fully ground to obtain a dry gel powder. Finally, the dry gel powder was heat-treated at 450°C for 60 minutes to obtain manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles.

[0028] Step 2: Add 0.001 mol of calcium nitrate (Ca(NO 3 ) 2 ∙4H 2 O), 0.002 mol indium nitrate (InCl 3 ∙4H 2 O) and a double excess of thioacetamide (0.008 mol CH 3 CSNH2 ) was dissolved in 80 ml of deionized water; 0.008 g of manganese zinc ferrite nanoparticles (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =50:1), and further stirred at room temperature for 30 minutes to obtain a suspension of the reaction mixture. Then, the solution was placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction (heating at 160°C for 12 hours). After the reaction was completed, the autoclave was naturally cooled to room temperature, centrifuged, washed and dried, and finally CaIn was obtained. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 Composite magnetic catalyst powder.

[0029] The electron microscope (SEM) image of the composite magnetic catalyst powder obtained in Example 1 is as follows: Figure 1 As shown, from Figure 1 As can be seen in the figure, CaIn 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 (CIS@MZF) composite magnetic catalysts do have two microscopic morphologies. Among them, the flower-shaped microspheres are CaIn 2 S 4 The photocatalytic material is composed of nanosheets stacked into flower balls with a diameter of 3 to 5 microns; and some 1 to 2 micron Mn 0.5 Zn 0.5 Fe 2 O 4 Nanoparticle aggregates. Obviously, CaIn 2 S 4 With Mn 0.5 Zn 0.5 Fe 2 O 4 A heterostructure is formed between them. Moreover, CaIn 2 S 4 With Mn 0.5 Zn 0.5 Fe 2 O 4 There is overlap between the band structures (e.g. Figure 1In the composite magnetic catalyst powder obtained in Example 1 of the present invention, the heterojunction with overlapping energy bands greatly suppresses the recombination of photogenerated carriers while reducing the effective bandwidth, thereby improving its photocatalytic performance.

[0030] like Figure 2 As shown, the present invention is to CaIn prepared in Example 1 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 The photocatalytic performance of the manganese zinc ferrite composite magnetic catalyst was analyzed. The present invention adopts the catalytic degradation of typical organic pollutants (dye: rhodamine B) to characterize the photocatalytic performance of the composite magnetic catalyst. Figure 2 The three photocatalysts synthesized by this invention are shown: pure CaIn 2 S 4 , composite catalyst 1 (mass ratio is CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =50:1) and composite catalyst 2 (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 = 20:1) Photocatalytic degradation performance of Rhodamine B. Figure 2 It is obvious that the photocatalytic performance of the composite photocatalyst is significantly higher than that of pure CaIn 2 S 4 For example, after 20 minutes of illumination, pure CaIn 2 S 4 The composite catalyst 1 decomposed 84% of the Rhodamine B, while the composite catalyst 1 decomposed 87% of the Rhodamine B, and the composite catalyst 2 decomposed 91% of the Rhodamine B. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 The photocatalytic performance of the composite magnetic catalyst has been significantly improved.

[0031] Comparative experiment like Figure 3 As shown, the present invention is to prepare the manganese zinc ferrite composite magnetic catalyst and pure CaIn 2 S 4After being evenly dispersed in aqueous solution, a comparative experiment was conducted using a ring magnet to absorb and recover the product. Figure 3 (a) and Figure 3 As can be seen from (b), pure CaIn 2 S 4 There is no magnetism, and magnetic adsorption has no effect on it; after 30 minutes of magnetic adsorption, the solution is still a turbid solution of suspended catalyst particles. In sharp contrast, Figure 3 (c) and Figure 3 As can be seen from (d), due to the presence of manganese-zinc ferrite particles with good magnetic properties, the solution of composite catalyst 2 becomes clear and transparent after a short period of magnet adsorption (2 minutes), indicating that the composite catalyst particles are completely adsorbed by the magnet. In this way, the photocatalyst can be quickly recovered and recycled, greatly reducing the material cost and time cost of photocatalytic applications.

[0032] Example 2 Step 1: According to the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) in a stoichiometric ratio of manganese nitrate (Mn(NO 3 ) 2 ·4H 2 O) 0.005 mol, zinc nitrate (Zn(NO 3 ) 2 6H 2 O) 0.005 mol, ferric nitrate (Fe(NO 3 ) 3 9H 2 O) 0.02 mol, add 100 ml of deionized water to dissolve, and stir at room temperature for 30 minutes to form a clear and transparent solution. Then, weigh 0.03 mol of ethylenediaminetetraacetic acid (EDTA) (the same as the total mass of metal ions) and add it to the above metal ion solution. Stir and dissolve it at 60°C for 6 hours to form a sol. The sol is heated and dehydrated at 100°C for 5 hours to obtain a dry gel, which is fully ground to obtain a dry gel powder. Finally, the dry gel powder is heat-treated at 450°C for 60 minutes to obtain manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles.

[0033] Step 2: Add 0.001 mol of calcium nitrate (Ca(NO 3 ) 2 ∙4H 2 O), 0.002 mol indium nitrate (InCl3 ∙4H 2 O) and a double excess of thioacetamide (0.008 mol CH 3 CSNH 2 ) was dissolved in 80 ml of deionized water; 0.02 g of manganese zinc ferrite nanoparticles (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =20:1), and further stirred at room temperature for 30 minutes to obtain a suspension of the reaction mixture. Then, the solution was placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction (heating at 160°C for 12 hours). After the reaction was completed, the autoclave was naturally cooled to room temperature, centrifuged, washed and dried, and finally CaIn was obtained. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 Composite magnetic catalyst powder.

[0034] Example 3 Step 1: According to the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) in a stoichiometric ratio of manganese nitrate (Mn(NO 3 ) 2 ·4H 2 O) 0.005 mol, zinc nitrate (Zn(NO 3 ) 2 6H 2 O) 0.005 mol, ferric nitrate (Fe(NO 3 ) 3 9H 2 O) 0.02 mol, add 100 ml of deionized water to dissolve, and stir at room temperature for 25 minutes to form a clear and transparent solution. Then, weigh 0.03 mol of ethylenediaminetetraacetic acid (EDTA) (the same as the total mass of metal ions) and add it to the above metal ion solution. Stir and dissolve it at 60°C for 8 hours to form a sol. The sol is heated and dehydrated at 80°C for 6 hours to obtain a dry gel, which is fully ground to obtain a dry gel powder. Finally, the dry gel powder is heat-treated at 400°C for 80 minutes to obtain manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles.

[0035] Step 2: Add 0.001 mol of calcium nitrate (Ca(NO 3 ) 2 ∙4H 2 O), 0.002 mol indium nitrate (InCl 3 ∙4H 2 O) and a double excess of thioacetamide (0.008 mol CH 3 CSNH 2 ) was dissolved in 80 ml of deionized water; 0.0057 g of manganese zinc ferrite nanoparticles (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =70:1), and further stirred at room temperature for 30 minutes to obtain a suspension of the reaction mixture. Then, the solution was placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction (heating at 160°C for 12 hours). After the reaction was completed, the autoclave was naturally cooled to room temperature, centrifuged, washed and dried, and finally CaIn was obtained. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 Composite magnetic catalyst powder.

[0036] Example 4 Step 1: According to the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) in a stoichiometric ratio of manganese nitrate (Mn(NO 3 ) 2 ·4H 2 O) 0.005 mol, zinc nitrate (Zn(NO 3 ) 2 6H 2 O) 0.005 mol, ferric nitrate (Fe(NO 3 ) 3 9H 2O) 0.02 mol, add 100 ml of deionized water to dissolve, and stir at room temperature for 25 minutes to form a clear and transparent solution. Then, weigh 0.03 mol of ethylenediaminetetraacetic acid (EDTA) (the same as the total mass of metal ions) and add it to the above metal ion solution. Stir and dissolve it at 80°C for 6 hours to form a sol. The sol is heated and dehydrated at 100°C for 5 hours to obtain a dry gel, which is fully ground to obtain a dry gel powder. Finally, the dry gel powder is heat-treated at 500°C for 60 minutes to obtain manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles.

[0037] Step 2: Add 0.001 mol of calcium nitrate (Ca(NO 3 ) 2 ∙4H 2 O), 0.002 mol indium nitrate (InCl 3 ∙4H 2 O) and a double excess of thioacetamide (0.008 mol CH 3 CSNH 2 ) was dissolved in 80 ml of deionized water; 0.04 g of manganese zinc ferrite nanoparticles (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =10:1), and further stirred at room temperature for 35 minutes to obtain a suspension of the reaction mixture. Then, the solution was placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction (heating at 170°C for 10 hours). After the reaction was completed, the autoclave was naturally cooled to room temperature, centrifuged, washed and dried, and finally CaIn was obtained. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 Composite magnetic catalyst powder.

[0038] Example 5 Step 1: According to the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) in a stoichiometric ratio of manganese nitrate (Mn(NO 3 ) 2 ·4H 2 O) 0.005 mol, zinc nitrate (Zn(NO3 ) 2 6H 2 O) 0.005 mol, ferric nitrate (Fe(NO 3 ) 3 9H 2 O) 0.02 mol, add 100 ml of deionized water to dissolve, and stir at room temperature for 30 minutes to form a clear and transparent solution. Then, weigh 0.03 mol of ethylenediaminetetraacetic acid (EDTA) (the same as the total mass of metal ions) and add it to the above metal ion solution. Stir and dissolve it at 60°C for 6 hours to form a sol. The sol is heated and dehydrated at 100°C for 5 hours to obtain a dry gel, which is fully ground to obtain a dry gel powder. Finally, the dry gel powder is heat-treated at 450°C for 60 minutes to obtain manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) nanoparticles.

[0039] Step 2: Add 0.001 mol of calcium nitrate (Ca(NO 3 ) 2 ∙4H 2 O), 0.002 mol indium nitrate (InCl 3 ∙4H 2 O) and a double excess of thioacetamide (0.008 mol CH 3 CSNH 2 ) was dissolved in 80 ml of deionized water; 0.01 g of manganese zinc ferrite nanoparticles (mass ratio of CaIn 2 S 4 :Mn 0.5 Zn 0.5 Fe 2 O 4 =40:1), and further stirred at room temperature for 30 minutes to obtain a suspension of the reaction mixture. Then, the solution was placed in a 100 ml polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction (heating at 160°C for 12 hours). After the reaction was completed, the autoclave was naturally cooled to room temperature, centrifuged, washed and dried, and finally CaIn was obtained. 2 S 4 @Mn 0.5 Zn 0.5 Fe 2 O 4 Composite magnetic catalyst powder.

[0040] In summary, the present invention provides a manganese-zinc ferrite composite magnetic catalyst and a preparation method thereof, using manganese-zinc ferrite (Mn 0.5 Zn 0.5 Fe2 O 4 ) magnetic particles and metal sulfide catalysts (CaIn 2 S 4 ) composite structure magnetic heterojunction catalytic material, by using a two-step hydrothermal method, and by setting specific experimental parameters and steps in the preparation process, the purpose is to comprehensively utilize manganese zinc ferrite materials to solve the environmental pollution problem generated in the production process of boundary elements (manganese zinc ferrite magnetic rings) for distribution network fault detection. By using the manganese zinc ferrite composite magnetic catalyst of the present invention, such sewage can be effectively treated. The CaIn of the present invention 2 S 4 With manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) After the magnetic particles are combined, they can form an effective heterostructure, which promotes the separation of photogenerated carriers and inhibits their recombination, thereby improving the photocatalytic performance of a single catalyst.

[0041] On the other hand, the manganese zinc ferrite (Mn 0.5 Zn 0.5 Fe 2 O 4 ) Magnetic particles, due to their magnetic properties, can realize the rapid recovery and recycling of catalysts on the basis of the above, greatly reducing the recovery cost and application cost of photocatalysts, and at the same time reducing the secondary pollution of water bodies by residual catalyst particles. Therefore, the present invention can not only improve the photocatalytic performance of a single catalyst, but also realize the rapid recycling of catalysts, promote the application of metal sulfide photocatalysts, and has good practicality.

[0042] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the specification and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a manganese-zinc ferrite composite magnetic catalyst, characterized in that: The steps include: S1. Add manganese nitrate, zinc nitrate and ferric nitrate into deionized water and mix and dissolve to form a metal ion solution, wherein: The molar ratio of manganese nitrate, zinc nitrate and iron nitrate is 1:1:4; S2, adding ethylenediaminetetraacetic acid having the same mass as the total mass of metal ions in the metal ion solution to the metal ion solution, stirring and dissolving to form a sol; heating and dehydrating the sol to obtain a dry gel, grinding the dry gel to obtain a powder; heat-treating the dry gel powder to obtain manganese zinc ferrite nanoparticles; S3, dissolving calcium nitrate, indium nitrate and thioacetamide in deionized water to produce CaIn2S4; then adding manganese zinc ferrite nanoparticles to obtain a suspension of a reaction mixture, wherein: The molar ratio of calcium nitrate, indium nitrate and thioacetamide is 1:2:8, and the mass ratio of the added manganese zinc ferrite nanoparticles to CaIn2S4 is 70:1-10:1; S4. The suspension of the reaction mixture is subjected to a hydrothermal reaction, and then subjected to subsequent extraction treatment to obtain a manganese-zinc-ferrite composite magnetic catalyst.

2. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In the above S1, manganese nitrate is Mn(NO3)2·4H2O, zinc nitrate is Zn(NO3)2·6H2O, and iron nitrate is Fe(NO3)3·9H2O.

3. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In S1, manganese nitrate, zinc nitrate and iron nitrate are added into deionized water, and then stirred at room temperature for 25 to 35 minutes to form a metal ion solution.

4. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In S2, after ethylenediaminetetraacetic acid is added to the metal ion solution, the solution is stirred and dissolved at a temperature of 60-80° C. for 6-8 hours to form a sol.

5. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In S2, the sol is heated and dehydrated to obtain a dry gel, specifically: The sol was heated and dehydrated at 80-100°C for 5-6 hours to obtain a dry gel.

6. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In S2, the parameters of the heat treatment are controlled as follows: The temperature is controlled at 400~500℃ and the time is controlled at 60~80 minutes.

7. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In the step S3, after adding the manganese zinc ferrite nanoparticles, stirring is performed at room temperature for 30 to 35 minutes to form a suspension of the reaction mixture.

8. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 1, characterized in that: In said S4, the hydrothermal reaction specifically comprises: The suspension of the reaction mixture is placed in a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, wherein the parameters of the hydrothermal reaction are controlled as follows: The temperature is controlled at 160~170°C and the time is controlled at 10~12 hours.

9. The method for preparing the manganese-zinc ferrite composite magnetic catalyst according to claim 8, characterized in that: In S4, the subsequent extraction process specifically includes: After the suspension of the reaction mixture is subjected to hydrothermal reaction, the autoclave is naturally cooled to room temperature, and the powder of manganese-zinc-ferrite composite magnetic catalyst is obtained through centrifugal filtration, washing and drying.

10. A manganese-zinc ferrite composite magnetic catalyst, characterized in that: The manganese-zinc-ferrite composite magnetic catalyst is prepared by the preparation method of the manganese-zinc-ferrite composite magnetic catalyst according to any one of claims 1 to 9; Manganese-zinc ferrite composite magnetic catalyst: CaIn2S4@Mn 0.5 Zn 0.5 Fe2O4, which contains Mn which has magnetic properties 0.5 Zn 0.5 Fe2O4 particle agglomerates, wherein: CaIn2S4 and Mn in the construction of manganese-zinc ferrite composite magnetic catalyst 0.5 Zn 0.5 The energy band structures of Fe2O4 overlap, forming a heterostructure between the two.

Citation Information

Cited By

  • A method for preparing a composite visible light catalyst from a zinc extraction tailing of a steelmaking furnace dust oxygen pressure sulfuric acid

    CN120662310B

  • Preparation process of high-frequency low-loss manganese zinc ferrite material

    CN120717782A